2020
DOI: 10.1186/s43019-020-00033-8
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison of single-bundle versus double-bundle anterior cruciate ligament reconstruction: a meta-analysis

Abstract: Background: Of the many issues regarding surgical techniques related to anterior cruciate ligament reconstruction (ACLR), single-bundle (SB) or double-bundle (DB) ACLR is one of the most debated topics. However, it is unclear which of the techniques yields better outcomes after ACLR for ACL injury. The purpose of this meta-analysis was to compare the benefits of SB versus DB ACLR in terms of biomechanical outcomes. Methods: The electronic databases MEDLINE, Embase, the Cochrane Central Register of Controlled T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 46 publications
0
35
0
Order By: Relevance
“…The principle behind this technique is to re-create the native ACL anatomy and restore the proper tension pattern of each bundle. Although biomechanical studies 29 , 34 have shown the technique to be superior, many studies 7 , 10 , 25 , 27 , 29 , 43 , 46 , 49 have shown no significant difference with respect to subjective clinical outcomes. Despite the potential benefits of double-bundle ACLR, single-bundle anatomic ACLR remains the preferred technique for surgeons in the United States and globally.…”
Section: Discussionmentioning
confidence: 99%
“…The principle behind this technique is to re-create the native ACL anatomy and restore the proper tension pattern of each bundle. Although biomechanical studies 29 , 34 have shown the technique to be superior, many studies 7 , 10 , 25 , 27 , 29 , 43 , 46 , 49 have shown no significant difference with respect to subjective clinical outcomes. Despite the potential benefits of double-bundle ACLR, single-bundle anatomic ACLR remains the preferred technique for surgeons in the United States and globally.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, the maximum ATT was observed in the ACL intact knee at 30° flexion and after anatomical DB reconstruction [ 28 ]. In some other studies, DB ACL reconstructions have shown closer biomechanics to an intact knee compared with SB reconstructions [ 8 , 14 , 29 ]. Tsai et al also showed similar result to our study in that the ATT after DB ACL reconstruction was smaller at a high flexion angle than after SB ACL reconstruction [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conventional single-bundle (SB) ACL reconstruction, the tunnels are made in the posterolateral (PL) tibial footprint and the anteromedial (AM) femoral footprint, resulting in a non-anatomical and more vertical direction than the native ACL, which cannot restore rotatory laxity [ 3 , 4 ]. Anatomical double-bundle (DB) ACL reconstruction shows superior biomechanical results, including both anterior and rotatory stability, compared to conventional non-anatomical SB ACL reconstruction [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biomechanically, it provides better valgus and internal rotation kinematics and anterior translational stability than the single-bundle reconstruction. 1 , 2 , 3 Clinical comparative studies provide several results from the equivalence of the 2 different reconstructions 4 , 5 , 6 to the superiority of double-bundle reconstruction in regard to rotational stability tests, revision reconstruction rate, or further osteoarthritis incidence rate. 7 , 8 , 9 …”
mentioning
confidence: 99%